Karakteristik sifat fisikokimia sabun cuci cair menggunakan sari lerak sebagai surfaktan alami - La Choviya Hawa; Umroh Qothrun Nada; Sumardi Hadi Sumarlan (AGROINTEK, 2023)
Lerak (Sapindus rarak Dc.) is an Asian plant that produces saponins, artificial surfactant, used as cleaning agent. Lerak has been used as traditional cleaning product because it is believed to maintain the color of the product, and also eco-friendly. The use of lerak as a traditional cleaning product is inefficient, so in this study lerak will processed as liquid laundry soap. This study conducted to determine the effect of lerak concentration (5 %, 7 % and 9 %) to the physicochemical properties of liquid laundry soap. This study used Randomized Block Design (RBD), analyzed by one way ANOVA and the next test used LSD test. Based on the research, lerak concentration were significantly different on pH, free fatty acids and clean ability of liquid laundry soap but were not significantly different on specific gravity, viscosity, foam stability of liquid laundry soap. The best treatment is liquid laundry soap with 7 % lerak concentration that have higher values of clean ability and viscosity. The addition of lerak concentration in liquid laundry is proven to increase their cleaning power and eco-friendly but will be constant at saturated level.